Предмет: Алгебра, автор: grfgfgfg1

Упростите выражение: tg(π/6)-tg(7π/12)/tg(π/6)tg(7π/12)+1

Ответы

Автор ответа: mathkot
0

Ответ:

\boxed{tg \ \left( \dfrac{\pi}{6}  \right) - \dfrac{tg \ \left( \dfrac{7\pi}{12}  \right)}{tg \ \left( \dfrac{7\pi}{12}  \right)tg \ \left( \dfrac{\pi}{6} \right )} + 1= \dfrac{3 - 2\sqrt{3} }{3} }

Объяснение:

tg \ \left( \dfrac{\pi}{6}  \right) - \dfrac{tg \ \left( \dfrac{7\pi}{12}  \right)}{tg \ \left( \dfrac{7\pi}{12}  \right)tg \ \left( \dfrac{\pi}{6} \right )} + 1 = tg \ \left( \dfrac{\pi}{6}  \right) - ctg \  \left( \dfrac{\pi}{6}  \right) + 1 = \dfrac{\sqrt{3} }{3} - \sqrt{3} + 1=

= \dfrac{\sqrt{3} }{3} - \sqrt{3} + 1 =\dfrac{\sqrt{3} - 3\sqrt{3}+ 3  }{3} = \dfrac{3 - 2\sqrt{3} }{3}

Похожие вопросы
Предмет: Геометрия, автор: Аноним
Предмет: Українська мова, автор: a0675617402